The Terms and Shapes of the Functions Necessary for Calculation of the Dissipated Power in the Problem of Indentation of a Punch Into a Two-Ply Material - Kaczorowski, J. (Engineering Transactions, 1983)
The paper presents a method of calculation of the majorant of the limit load for the example of a punch into a semispace consisting of an isotropic laminar material. Proving the validity of the suggested theorems and lemma for a selected class of strain types, the calculation of the minimum dissipated power has been significantly simplified. The problem of finding the minimum of the functional has been reduced to the search for the minimum of a function of a single variable.